2023
DOI: 10.3389/fmed.2023.1310391
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the impact of human blood metabolites on the Sepsis development and progression: a study utilizing two-sample Mendelian randomization

Zhongqi Zhang,
Yu Yin,
Tingzhen Chen
et al.

Abstract: BackgroundExisting data suggests a potential link between human blood metabolites and sepsis, yet the precise cause-and-effect relationship remains elusive. By using a two-sample Mendelian randomization (MR) analysis, this study aims to establish a causal link between human blood metabolites and sepsis.MethodsA two-sample MR analysis was employed to investigate the relationship between blood metabolites and sepsis. To assess the causal connection between sepsis and human blood metabolites, five different MR me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Additionally, we explored the potential mediators between mental illness and sepsis. Previous studies have shown that mental illness leads to changes in inflammatory factors, blood metabolites and gut microbiome, which in turn are associated with sepsis (23)(24)(25)(26)(27)(28), and several MR studies have recently demonstrated the relationship between blood metabolites and sepsis (29,30). Therefore, mediation MR analysis was applied to explore the mediating pathway among mental illnesses and sepsis via the phenotypes of inflammatory factors, blood metabolites and gut microbiome.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we explored the potential mediators between mental illness and sepsis. Previous studies have shown that mental illness leads to changes in inflammatory factors, blood metabolites and gut microbiome, which in turn are associated with sepsis (23)(24)(25)(26)(27)(28), and several MR studies have recently demonstrated the relationship between blood metabolites and sepsis (29,30). Therefore, mediation MR analysis was applied to explore the mediating pathway among mental illnesses and sepsis via the phenotypes of inflammatory factors, blood metabolites and gut microbiome.…”
Section: Introductionmentioning
confidence: 99%